Impact of emotional intelligence on Transformational leadership of Academic heads of state universities in Eastern province of Sri Lanka - Rajee, R.F.; Sareena, U.M.A.G.; Kengatharan, N. (My University, 2020)
Emotional intelligence has developed gradually popular as a measure for discovering possibly effective leaders, and as an instrument for developing effective leadership skills. Regardless of this popularity, however, there is little experimental research that confirms the usefulness of emotional intelligence in these areas. The aim of this paper is to discover the connection between emotional intelligence and transformational leadership. The research population consisted of 117 academic heads who are employed in state universities in Eastern province of Sri Lanka. Since the population size was small, total population sampling method was used. . Data gathering was done by using self-administered questionnaire. The study aimed to 117 respondents from which 98 respondents were realized and recorded around 82% of response rate. The correlation between emotional intelligence and transformational leadership was investigated in this study of academic heads. The results showed that there is a strong positive correlation (r= 0.717) between EI and TL which was significant at 0.01 level. The result of simple regression study revealed that, R square and adjusted R square values exposed as 0.514 and 0.509 respectively, states around 51% of the variations on transformational leadership explain by the emotional intelligence. Further researchers can reproduce this study with a large number of sample sizes by concerning other provinces of Sri Lanka and covering both private and public universities. Further, this study imply that proper strategies should be formulated by the universities in order to enhance, emotional intelligence level and to advance the leader‟s abilities and skills in the day-to-day contacts with all subordinates.
Keywords: Emotional intelligence; Transformational leadership and academic heads